Ab initio study of structural, energetic, and electronic properties of two-dimensional transition metal dichalcogenides - Besse, Rafael (2021)
The advances in techniques for the isolation and synthesis of two-dimensional materials have opened new paths for the investigation of novel physical phenomena and properties, with great potential for technological innovation. In this context, transition metal dichalcogenides form a prominent class of compounds, due to their unique electronic and optical properties. This thesis aims to contribute to the understanding of the physical properties of two-dimensional transition metal dichalcogenides, studying a wide variety of systems by means of calculations based on density functional theory and time-dependent density functional theory combined with molecular dynamics. The analysis of relative phase stability in MoSe2 showed that the Peierls transition mechanism leads to the stabilization of the distorted octahedral phase, and a phase preference transition induced by the nanoflakes sizes was demonstrated. By investigating two-dimensional materials based on dichalcogenides of transition metals of groups 8 to 11, it was found that weak interlayer binding, typical of two-dimensional materials, occurs in the systems with transition metals of groups 8 and 10, whereas a strong contribution of chemical bonds was observed in the remaining materials. The identified semiconductor monolayers also have transition metals from groups 8 and 10, and the chemical trends of band offsets could be explained and employed with Anderson´s rule to predict junction types of heterobilayers. With the examples of the heterobilayers of MQ2 (M = Mo, Ni, Pt; Q = S, Se), it was found that although interlayer binding is dominated by weak interactions, interlayer coupling can significantly influence band gaps beyond the approximation of Anderson´s rule. Two mechanisms are crucial for these effects, namely, the interlayer hybridization of electron states and the formation of electric dipole at the interface, which was explained by a simple physical model. In the MoS2/PtSe2 heterobilayer, it was observed that a photoexcitation across the band gap of MoS2 generates electron transfer to the PtSe2 layer at a faster rate than hole transfer, leading to an effective charge separation, despite the type-I band alignment. Both carriers transfers are influenced by the level crossings induced by the interfacial dipole caused by the imbalance in charge transfer.